Urban elementary school principals and their functions in action research identification, analysis and a suggested action research project - Melocoton, Zayda A. 1923- (s.n.], 1969)
the study presents the action research functions of urban elementary school principals. The main objective of the study is to provide baseline empirical data on one aspect of a principal's function and to infer from what is presently being done and how the research functions can be implemented in a suggested action research project. The study aims to give district supervisors and superintendents of schools insight on how elementary school principals can best contribute to the improvement of action research projects.